Morphology- and size-dependent spectroscopic properties of Eu(3+)-doped Gd(2)O(3) colloidal nanocrystals - Wawrzynczyk, Dominika (Springer Netherlands, 2014)
The synthesis, morphological characterization, and optical properties of colloidal, Eu(III) doped Gd(2)O(3) nanoparticles with different sizes and shapes are presented. Utilizing wet chemical techniques and various synthesis routes, we were able to obtain spherical, nanodisk, nanotripod, and nanotriangle-like morphology of Gd(2)O(3):Eu(3+) nanoparticles. Various concentrations of Eu(3+) ions in the crystal matrix of the nanoparticles were tested in order to establish the levels at which the concentration quenching effect is negligible. Based on the luminescence spectra, luminescence lifetimes and optical parameters, which were calculated using the simplified Judd–Ofelt theory, correlations between the Gd(2)O(3) nanoparticles morphology and Eu(3+) ions luminescence were established, and allowed to predict the theoretical maximum quantum efficiency to reach from 61 to 98 %. We have also discussed the impact of the crystal structure of Gd(2)O(3) nanoparticles, as well as coordinating environment of luminescent ions located at the surface, on the emission spectra. With the use of a tunable femtosecond laser system and the Z-scan measurement technique, the values of the effective two-photon absorption cross-section in the wavelength range from 550 to 1,200 nm were also calculated. The nonlinear optical measurements revealed maximum multi-photon absorption in the wavelength range from 600 to 750 nm.